The Role of FKBP5 in Mood Disorders: Action of FKBP5 on Steroid Hormone Receptors Leads to Questions About its Evolutionary Importance - O’Leary III, John C.; Zhang, Bo; Koren III, John; Blair, Laura; A. Dickey, Chad (CNS & Neurological Disorders - Drug Targets, 2013)
Research on the FKBP5 gene and FKBP51 protein has more than doubled since the discovery that polymorphisms in this gene could alter treatment outcomes and depressive behavior in humans. This coincided with other data suggesting that the stress hormone axis contributes to the development of numerous mental illnesses. As a result, FKBP51 now lies at the heart of the research of many stress related psychiatric disorders, which has led to advances in the understanding of this protein and its role in humans and in animal models. Specifically, FKBP5-/- mice and a naturally existing overexpression of FKBP5 in 3 genera of new world monkeys have helped understand the effects of FKBP5 in vivo. This review will highlight these finding as well as discuss the current evolutionary need for the FKBP5 gene.
Keywords: depression